The relevance of miRNAs as promising biomarkers in lip cancer - Assao, Agnes; Domingues, Maria Aparecida Custodio [UNESP]; Minicucci, Eliana Maria [UNESP]; Marchi, Fabio Albuquerque; Coutinho-Camillo, Claudia Malheiros; Oliveira, Denise Tostes (Springer, 2021)
Objectives This study aimed to analyze the expression of miR-181b, miR-21, miR-31, and miR-345 in actinic cheilitis with and without epithelial dysplasia and lower lip squamous cell carcinomas, and to verify if the deregulated expression of these miRNAs would be indicative of malignant transformation. Materials and methods The sample was selected from formalin-fixed paraffin-embedded tissues of 19 actinic cheilitis without epithelial dysplasia, 32 actinic cheilitis with epithelial dysplasia, 42 lower lip squamous cell carcinomas, and 10 nonaltered oral mucosa of the lip. The microRNA (miR, miRNA) expression was quantified by real-time RT-PCR and the expression of the selected miRNAs among the groups of actinic cheilitis and lower lip cancer was compared by chi-square. Results A higher expression of miR-181b, miR-31, and miR-345 was found in actinic cheilitis without epithelial dysplasia in comparison to that in actinic cheilitis with epithelial dysplasia and with lower lip cancer. There were no differences in miR-21 expression between actinic cheilitis and lower lip cancer. Hierarchical clustering analysis showed a tendency for a downregulation of miR-181b, miR-21, miR-31, and miR-345 in most patients with lower lip cancers. Conclusions The upregulation of miR-181b, miR-31, and miR-345 expression in actinic cheilitis without epithelial dysplasia and the decrease in the expression of these miRNAs in actinic cheilitis with epithelial dysplasia and in lower lip cancer are potential biomarkers of malignant progression.
Keywords: Oral cancer; miR; Lip cancer; Actinic cheilitis